Research on the valuation of the net social benefit of reuse (BLSR) in the municipality of Paragominas, Pará - Pereira Junior, Antônio; Teixeira Barros, Bruno; Costa Santos, Pedro (Seven Editora, 2023)
Several initiatives culminate in environmental gains, such as recycling and reuse. This provides savings regarding natural inputs, especially minerals and vegetable cellulose. In this sense, the present work aims to investigate the Net Social Benefit of Reuse (BLSR) of steel, aluminum, paper, plastic and glass, which the municipality of Paragominas does not have with the poor management of RS. The method used was based on two hypotheses, (1) the scrap market operates in perfect competition; (2) true opportunity cost. Five classes of municipal waste were analyzed: steel, aluminum, paper, glass, and plastics, regarding their reuse and the financial resources generated by this action. The data obtained and analyzed indicated that, among the five classes analyzed for the municipality of Paragominas, plastic presents the highest BLSR, in both hypotheses (H1= R 511.77; H2 = R 433.04); and that all classes of waste present a potential benefit of up to R 17,542,924.95/year to the municipality of Paragominas. DOI: https://doi.org/10.56238/tfisdwv1-145